“Masters Speak: Management Education In India” - Nangia, Vinay Kumar; Sharma, Vinay; Agrawal , Rajat; Mahajan, Ritika; Singh , Bushra S P (Gyan Management Journal, 2019)
This book presents first hand conversations with some of the living legends and veterans who  shaped the development of management education in India. These include Professors Abad Ahmad,  Ashoka Chandra, Charan D. Wadhva, D. M. Pestonjee, Dilip K. Bandyopadhyay, Ishwar Dayal, J.  Philip, K. R. S. Murthy, Krishna Kumar, Mangesh G. Korgaonker, N. R. Sheth, Pramod Verma, Pradip  N. Khandwalla, Pritam Singh, Rajan Saxena, S. Neelamegham, Samuel Paul and VinayshilGautam. The smooth precise questions, thought-provoking follow ups and interesting anecdotes capture the  essence of teaching from the best in the field. The interview with the thought leaders and institution  builders offers to its readers, their perspective of the purpose and conception of management  education in India, development of some of the most important B-schools of the country like Delhi  University, IIMs, bird's eye view of present state of management education, role of leaders in  institution building, evolution of management education, major milestones, qualification for faculty  members for management institutes, unique characteristics of management education, accreditation, common admission tests etc.
Keywords: veterans; development; management; education; qualification; accreditation